Dietary supplementation with Citrullus lanatus whole fruit and pulp possesses antioxidant effects in oxidative stressed rats - OKOLO, IJEOMA; Audu, Funmilola (FUDMA Journal of Sciences, 2025)
The pulp of Citrullus lanatus is mostly consumed while the seeds and rind are discarded. This study evaluated the effect of a diet supplemented with C. lanatus whole fruit and pulp against acetaminophen induced oxidative stress in rats. Whole fruits and pulp were cut into small sizes, air-dried and grounded. Twenty rats were divided into four groups of five each. Group 1(normal control) and 2 (negative control) consumed normal rat chow while groups 3 and 4 consumed normal rat chow supplemented with 5% C. lanatus whole fruit and pulp respectively for 21 days. Haematological parameters were monitored weekly. On the 21st day, a single dose of acetaminophen (2g/kg) was administered to groups 2, 3, and 4. All rats were humanely sacrificed 12 hours later. Haematological parameters and antioxidant enzymes were measured in the blood and liver respectively Results showed that both supplementation with 5% whole fruit and pulp had no significant (p>0.05) effect on haematological parameters. However, acetaminophen overdose caused a significant (p
Keywords: Acetaminophen; Citrullus lanatus; Dietary supplementation; Oxidative stress; Haematology